Inhibition of renal glucose reabsorption as a novel treatment for diabetes patients - Cersosimo,Eugenio (2014)
The importance of the kidney in glucose homeostasis has been recognized for many years. Recent observations indicating a greater role of renal glucose metabolism in various physiologic and pathologic conditions have rekindled the interest in renal glucose handling as a potential target for the treatment of diabetes. The enormous capacity of the proximal tubular cells to reabsorb the filtered glucose load entirely, utilizing the sodium-glucose co-transporter system (primarily SGLT-2), became the focus of attention. Original studies conducted in experimental animals with the nonspecific SGLT inhibitor phlorizin showed that hyperglycemia after pancreatectomy decreased as a result of forced glycosuria. Subsequently, several compounds with more selective SGLT-2 inhibition properties (“second-generation”) were developed. Some agents made it into pre-clinical and clinical trials and a few have already been approved for commercial use in the treatment of type 2 diabetes. In general, a 6-month period of therapy with SGLT-2 inhibitors is followed by a mean urinary glucose excretion rate of ~80 g/day accompanied by a decline in fasting and postprandial glucose with average decreases in HgA1C ~1.0%. Concomitant body weight loss and a mild but consistent drop in blood pressure also have been reported. In contrast, transient polyuria, thirst with dehydration and occasional hypotension have been described early in the treatment. In addition, a significant increase in the occurrence of uro-genital infections, particularly in women has been documented with the use of SGLT-2 inhibitors. Conclusion: Although long-term cardiovascular, renal and bone/mineral effects are unknown SGLT-2 inhibitors, if used with caution and in the proper patient provide a unique insulin-independent therapeutic option in the management of obese type 2 diabetes patients.